2016
DOI: 10.1016/j.ajpath.2016.03.021
|View full text |Cite
|
Sign up to set email alerts
|

The Complement Regulatory Protein CD46 Deficient Mouse Spontaneously Develops Dry-Type Age-Related Macular Degeneration–Like Phenotype

Abstract: In the mouse, membrane cofactor protein (CD46), a key regulator of the alternative pathway of the complement system, is only expressed in the eye and on the inner acrosomal membrane of spermatozoa. We noted that although Cd46 À/À mice have normal systemic alternative pathway activating ability, lack of CD46 leads to dysregulated complement activation in the eye, as evidenced by increased deposition of C5b-9 in the retinal pigment epithelium (RPE) and choroid. A knockout of CD46 induced the following cardinal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 86 publications
(72 reference statements)
2
22
0
Order By: Relevance
“…C3ar1 tm1Cge mutants show very slow PR degeneration with about 20% loss at 14 months [423]. Cd46 tm1Atk show different rates of PR nuclei loss in male and female mice with 23% and 31% at 12 months of age, respectively [424]. Mutations in Cx3cr1, normally expressed in immune cells including microglia, were associated with PR cell loss.…”
Section: Category 11: Immune Responsementioning
confidence: 99%
“…C3ar1 tm1Cge mutants show very slow PR degeneration with about 20% loss at 14 months [423]. Cd46 tm1Atk show different rates of PR nuclei loss in male and female mice with 23% and 31% at 12 months of age, respectively [424]. Mutations in Cx3cr1, normally expressed in immune cells including microglia, were associated with PR cell loss.…”
Section: Category 11: Immune Responsementioning
confidence: 99%
“…However, human genetic studies have not identified an association between CD46 mutations and AMD. Furthermore, a spontaneously occurring mouse model of AMD has been described (9496). This genetic model demonstrates a multifocal, bilateral spontaneous choroidal neovascularization, which leads to early, persistent neovascular lesions that result in death.…”
Section: Membrane Cofactor Protein Mutationsmentioning
confidence: 99%
“…Increasing evidence has shown that inflammatory processes, especially the complement activation pathway, may play a major role in the pathogenesis of AMD [48,49]. Thus, we can regulate complement and inflammatory system to delay the development of dry AMD [50,51]. Next, to identify some novel detection markers and target drugs for different types of AMD is the current and future research focus on the direction.…”
Section: Discussionmentioning
confidence: 99%